The Liver histopathology structure of Wistar rats on the acute toxicity test of Kapulaga Seeds extract (Amomum cardamomum) - Ratih Dewi Yudhani; Rizka Hendriyani; Riza Novierta Pesik (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2020)
One-third of the Indonesian population uses herbs for alternative medicine empirically. One of them is Kapulaga (Amomum cardamomum) which known as a spice and traditionally used for the treatment of rheumatic, fever, cough, sore throat, and mouth odor. The clinical use of herbs must be supported by scientific evidenced-based and its safety profile. The risk of exposure to a substance in humans can be identified through the toxicity tests on animals. The liver histopathological structure is one of the parameters of the acute toxicity test. This study to determine the acute toxicity of Kapulaga seeds extract (Amomum cardamomum) based on the liver histopathological structure of Wistar rats. The sample selection based on inclusion and exclusion criteria in the OECD 420 guideline. The research consisted of a preliminary and the main test. One rat was used in the preliminary test with an initial dose of cardamom seed extract 300 mg/kg BW and followed by a maximum dose of 2000 mg/kg BW after 48 hours. The main test used 10 rats that were randomly divided into control and treatment groups. Based on the result of the preliminary test, the treatment group was given a single dose of cardamom seed extract 2000mg /kg BW, whilst the control group was given distilled water. Observations of any toxic signs or dead were conducted every 30 minutes in the first 4 hours and continued once per day until 14thday. Assessment of the degree of liver damage was done using the liver damaged scoring and compared using the Mann Whitney test (α = 0.05). The average liver damage score of control and treatment groups is 0.96 ± 0,856 and 0.96 ± 0,604, respectively, and did not show any statistically significant differences (p>0,05). Kapulagaseeds (Amomum cardamomum) had no acute toxic effect based on the liver histopathological structure of Wistar rats.